European Approaches to Stopping Islamophobia are Inadequate: Lessons for Canadians Combating Anti-Muslim Racism and Hatred - Hassina Alizai (Journal of Hate Studies, 2023)
The United Kingdom, France, and Spain have in common a large and growing Muslim population. The influx of immigrants and refugees has left many European states fearful of Muslim migrants because they perceive potential increases in terrorism and job insecurity, which would have significant social and economic policy implications. European governments have sought to strengthen security measures and immigration laws, often with consequences that disproportionately and negatively affect Muslims. At the same time, European governments have increased their efforts to address Islamophobia and improve Muslim integration, partly in response to the growth in the reporting of anti-Muslim hate crimes. Each of the aforementioned states has adopted different approaches to tackle issues affecting Muslim communities. Although some of the countries (e.g., Spain) have taken positive approaches in the fight against Islamophobia, others (e.g., France) pave the way for social disintegration and segregation by entrenching low socioeconomic status, passing discriminatory laws, and blaming violent attacks on Muslims as a whole. It appears that the European nations examined in this comparative analysis have failed, to varying degrees upholding values of equitable diversity and encouraging meaningful dialogue with Muslim organizations. Their approaches demonstrate a clear lack of adequate governmental response to growing levels of Islamophobia.